Effectiveness of Childbirth Education and Hypnobirthing Assistance in Improving Labor Outcome - Himawati, Yulia; Demartoto, Argyo; Murti, Bhisma (Journal of Maternal and Child Health, 2024)
Background: Childbirth education and assistance with hypnobirthing is an autohypnosis technique, namely an effort to instill positive intentions through suggestion into the soul or subconscious mind during pregnancy and preparation for childbirth. This study aims to analyze the effectiveness of childbirth education and assistance with hypnobirthing in improving childbirth outcomes. Subjects dan Methode: The Randomized Controlled Trial (RCT) study was conducted at the Pratama D'Maryam Clinic, Yogyakarta from August to December 2023. A total of 154 pregnant women were selected for this study. Dependent variables are anxiety, depression, complications, and delivery time. The independent variables are childbirth education and assistance with hypnobirthing. Therapy is given 2 times a week with a duration of 3 hours. The study instrument is a questionnaire. Data analysis used Independent T-Test. Results: Providing childbirth education accompanied by assistance with hypnobirthing is effective in reducing anxiety levels in pregnant women (Effect Size= 1.22; p<0.001), reducing depression levels (Effect Size= 1.19; p<0.001), and shortening labor time (Effect Size= 0.08; p = 0.016). Conclusion: Providing childbirth education accompanied by assistance with hypnobirthing is effective in reducing anxiety levels in pregnant women, reducing depression levels, and shortening labor time.